63.3k views
0 votes
Expand and simplify (2x+1) (x-2) (x+3)

User Wilmer
by
5.6k points

2 Answers

3 votes

Answer:

2x^3 + 3x^2 - 11x - 6.

Explanation:

(2x+1) (x-2) (x+3)

= (2x + 1)[x(x + 3)-2(x + 3)]

= (2x + 1)(x^2 + x - 6)

= 2x(x^2 + x - 6) + 1(x^2 + x - 6)

= 2x^3 + 2x^2 - 12x + x^2 + x - 6

= 2x^3 + 3x^2 - 11x - 6.

User Susanne Peng
by
5.8k points
4 votes

Good morning,

Answer:

=2x³+3x²-11x-6.

Explanation:

(2x+1) (x-2) (x+3)

= (2x+1) [(x-2) (x+3)]

= (2x+1) [x²+3x-2x-6]

= (2x+1) [x²+x—6]

= 2x³+2x²-12x+x²+x-6

=2x³+3x²-11x-6.

:)

User Dilly
by
5.6k points